Adjuvant S-1 plus endocrine therapy for oestrogen receptor-positive, HER2-negative, primary breast cancer: a multicentre, open-label, randomised, controlled, phase 3 trial. Issue 1 (January 2021) - Toi, Masakazu; Imoto, Shigeru; Ishida, Takanori; Ito, Yoshinori; Iwata, Hiroji; Masuda, Norikazu; Mukai, Hirofumi; Saji, Shigehira; Shimizu, Akira; Ikeda, Takafumi; Haga, Hironori; Saeki, Toshiaki; et al.
Summary: Background: Oral fluoropyrimidines, such as S-1, have been shown to have a role in controlling disease progression in metastatic breast cancer. We examined adjuvant treatment with S-1 in patients with oestrogen receptor (ER)-positive and HER2-negative primary breast cancer. Methods: We did a multicentre, open-label, randomised, controlled, phase 3 trial in 139 sites (137 hospitals and two clinics). Eligible patients were women aged 20–75 years with histologically diagnosed stage I to IIIB invasive breast cancer (intermediate to high risk of recurrence). Patients were temporarily registered at participating institutions and biopsy or surgical samples were collected and sent for central pathological assessment. Patients received 5 years of standard adjuvant endocrine therapy (selective oestrogen receptor modulators with or without ovarian suppression and aromatase inhibitors) with or without 1 year of S-1. Oral S-1 80–120 mg/day was administered twice a day for 14 days with 7 days off. Randomisation (1:1) using the minimisation method was done with six stratification factors (age, axillary lymph node metastasis at surgery or sentinel lymph node biopsy, preoperative or postoperative (neoadjuvant or adjuvant) chemotherapy, preoperative endocrine therapy, proportion of ER-positive cells, and study site). The primary endpoint was invasive disease-free survival, in the full analysis set (all randomly assigned patients, excluding those with significant protocol deviations). The safety analysis set consisted of all patients who received at least one dose of study treatment. Here, we report the results from the interim analysis at the data cutoff date Jan 31, 2019. This trial is registered with Japan Registry of Clinical Trials, jRCTs051180057, and the University hospital Medical Information Network, UMIN000003969. Findings: Between Feb 1, 2012, and Feb 1, 2016, 1930 patients were enrolled in the full analysis set, 957 (50%) received endocrine therapy plus S-1 and 973 (50%) received endocrine therapy alone. Median follow-up was 52·2 months (IQR 42·1–58·9). 155 (16%) patients in the endocrine therapy alone group and in 101 (11%) patients in the endocrine therapy plus S-1 group had invasive disease-free survival events (hazard ratio 0·63, 95% CI 0·49–0·81, p=0·0003). As the primary endpoint was met at interim analysis, the trial was terminated early. The most common grade 3 or worse adverse events were decreased neutrophil count (72 [8%] of 954 patients in the endocrine therapy plus S-1 group vs seven [1%] of 970 patients in the endocrine therapy alone group), diarrhoea (18 [2%] vs none), decreased white blood cells (15 [2%] vs two [<1%]), and fatigue (six [<1%] vs none). Serious adverse events were reported in nine (1%) of 970 patients in the endocrine therapy alone group and 25 (3%) of 954 patients in the endocrine therapy plus S-1 group. There was one (<1%) possible treatment-related death in the endocrine therapy plus S-1 group due to suspected pulmonary artery thrombosis. Interpretation: These data suggest that this combination of S-1 with endocrine therapy could be a potential treatment option for this intermediate and high-risk group of patients with ER-positive, HER2-negative primary breast cancer. Funding: Public Health Research Foundation (Japan), Taiho Pharmaceutical.